Mediterranean animal production: development or decline ? - Rancourt M. de; Mottet A. (Mediterranean livestock production: uncertainties and opportunities, 2008)
The Mediterranean region has a very rich and long history of trade across the Mediterranean Sea in many industries and particularly in animal productions. The Mediterranean animal industries, and ruminants in particular, have some common traits such as the importance of pastoral systems, light and young carcass productions, numerous labelled and regional products and the predominance of small versus large ruminants. However EU and non-EU countries differ significantly in terms of standard of living, market protection, public subsidies or types of production systems. To try to analyse the potential development of these Mediterranean countries, we will overview some main issues of animal production. The development of Mediterranean countries livestock production will be conditioned by the animal farmers' ability to group together for production and/or commercialisation and to communicate more between Southern and Northern countries.
2. Seminar of the Scientific-Professional Network on Mediterranean Livestock Farming (RME), 2006/05/18-20, Zaragoza, (Spain)